Linguagem, letramento e ideologia na comunidade: análise de discurso crítica e mudança social - Costa, Pedro H. H. da; Zanon, Marian R.; Rios, Guilherme V.; Bazzo, Adriana C.; Santos, Carmelita; Magalhães, Izabel (Cadernos de Linguagem e Sociedade, 2010)
The purpose of this paper is to discuss what people say about literacy in real text and in the relation holding among texts (intertextuality) in discursive literacy practices. An attempt is made to integrate the linguistic theory of Criticai Discourse Analysis with anthropological studies of literacy practices. The data analysed is part of a larger project concerned with the discourse of education. The data consists of texts written by learners and teachers in a community adult literacy programme. Some of these texts, among which is a short play, were written to celebrate the literacy teacher’s day. The analysis of the play shows that an identity of ’trespassers’ is constructed for the original migrant group that went to live in the community. In addition, the analysis of learners’ texts indicates that learners often reproduce the dominant educational practice in Brazil, which is linked to hegemonic social groups. This is achieved by means of a ’disciplinary subject position’ which is constituted for them. The analysis of the play suggests, however, that learners are aware of the unequal power relations to which they are subjected. Thus, a second subject position is defined in the play, that of the ’community subject’. Finally, this paper proposes the adoption of the principies subsumed in Criticai Language Awareness for the study of adult literacy, and further as a possible contribution to solve Brazilian educational problems.